2006
DOI: 10.1021/ie060239+
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Dyes, Sugars, and Amino Acids from NaCl Solutions Using Multilayer Polyelectrolyte Nanofiltration Membranes

Abstract: Several recent studies demonstrated highly selective ion and neutral molecule transport through multilayer polyelectrolyte nanofiltration (NF) membranes. This work examines the potential of such membranes in the selective removal of dyes, sucrose, and amino acids from NaCl solutions. Remarkably, simple deposition of 4.5-bilayer poly(styrenesulfonate) (PSS)/poly(allylamine hydrochloride) (PAH) films on porous alumina supports yields membranes that exhibit NaCl/sucrose selectivities of ∼130 and NaCl/dye selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 40 publications
3
58
0
1
Order By: Relevance
“…It was reported that nanofiltration technology could separate low molecular weight solutes from inorganic salt solutions (Bao et al, 2013;Luo et al, 2009;Hong et al, 2006). Nanofiltration membranes have the advantages of providing a high water flux at low operating pressure and maintaining a high salt and organic matter rejection (Hilal et al, 2005;Moravia et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that nanofiltration technology could separate low molecular weight solutes from inorganic salt solutions (Bao et al, 2013;Luo et al, 2009;Hong et al, 2006). Nanofiltration membranes have the advantages of providing a high water flux at low operating pressure and maintaining a high salt and organic matter rejection (Hilal et al, 2005;Moravia et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…PEM's can provide membranes with antifouling functionalities [11,12,[14][15][16][17][18], as well as act as the separation (skin) layer for NF membranes [19]. Most of the previous studies on PEM based NF membranes, utilized flat sheet membrane supports as reported for example by Bruening et al [20][21][22][23][24][25] and Tieke et al [26,27]. However, the hollow fiber configuration would offer a higher productivity [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This pressure-driven membrane process has received considerable attention in the industry due to its unique ability to remove products from process streams, especially low molecular weight solutes (e.g. glucose, saccharides, amino acids, and peptides) [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%